Aramaic magic bowls in the Vorderasiatisches Museum in Berlin : descriptive list and edition of selected texts - Bhayro, Siam. (Magical and Religious Literature of Late Antiquity, 2018)
The collection of Aramaic magic bowls and related objects in the Vorderasiatisches Museum in Berlin is one of the most important in the world. This book presents a description of each object and its contents, including details of users and other names, biblical quotations, parallel texts, and linguistic features. Combined with the detailed indices, the present volume makes the Berlin collection accessible for further research. Furthermore, sixteen texts, which are representative of the whole collection, are edited. This book results from an impressive collaboration between Siam Bhayro, James Nathan Ford, Dan Levene, and Ortal-Paz Saar, with further contributions by Matthew Morgenstern, Marco Moriggi, and Naama Vilozny, and will be of interest for all those engaged in the study of these fascinating objects.